Effects of adropin on learning and memory in rats tested in the Morris water maze. Issue 4 (31st December 2021) - Ozkan, Ayse; Aslan, Mutay Aydin; Sinen, Osman; Munzuroglu, Mustafa; Derin, Narin; Parlak, Hande; Bulbul, Mehmet; Agar, Aysel
Abstract: Adropin is a secreted peptide, which is composed of 43 amino acids and shows an effective role in regulating energy metabolism and insulin resistance. Motor coordination and locomotor activity were improved by adropin in the cerebellum. However, it is not known whether adropin administration has an effect on spatial learning and memory. In this study, we investigated the effect of adropin on spatial learning and memory and characterized the biochemical properties of adropin in the hippocampus. Thirty male Sprague–Dawley rats were randomly divided into two groups as control and adropin groups. The control group received 0.9% NaCl intracerebroventricular for 6 days, while the adropin groups received 1 nmol of adropin dissolved in 0.9% NaCl (for 6 days). The Morris water maze, Y maze, and object location recognition tests were performed to evaluate learning and memory. Also, the locomotor activity tests were measured to assess the motor function. The expression of Akt, phospho‐Akt, CREB, phospho‐CREB, Erk1/2, phospho‐Erk1/2, glycogen synthase kinase 3 β (GSK3β), phospho‐GSK3β, brain‐derived neurotrophic factor (BDNF), and N ‐methyl‐d ‐aspartate receptor NR2B subunit were determined in the hippocampal tissues by using western blot. Behavior tests showed that adropin significantly increase spatial memory performance. Meanwhile, the western blot analyses revealed that the phosphorylated form of the Akt and CREB were enhanced with adropin administration in the hippocampus. Also, the expression of BDNF showed an enhancement in adropin group in comparison to the control group. In conclusion, we have shown for the first time that adropin exerts its enhancing effect on spatial memory capacity through Akt/CREB/BDNF signaling pathways.